Total Endovascular Repair With Parallel Stent-Grafts for Postdissection Thoracoabdominal Aneurysm After Prior Proximal Repair. (October 2019) - Liu, Junjun; Li, Zhenjiang; Feng, Jiaxuan; Zhou, Jian; Zhao, Zhiqing; Bao, Xianhao; Zhao, Yuxi; Xu, Ziyi; Wu, Jianlie; Wang, Haofu; Feng, Rui; Jing, Zaiping
Purpose: To evaluate the safety and efficacy of total endovascular repair with parallel stent-grafts for postoperative residual dissection thoracoabdominal aortic aneurysm (TAAA).Materials and Methods: A retrospective study was undertaken of 21 patients (mean age 64.0±12.5 years; 17 men) undergoing total endovascular therapy with parallel stent-grafts for postdissection TAAA after prior proximal repair between 2014 and 2016. The preoperative minimum true lumen diameter was 12.3±4.8 mm and the mean extent of dissection was 248.1±48.2 mm. Pre-, intra-, and postoperative medical records were reviewed to assess technical success, spinal cord ischemia, patency of target branch arteries, endoleak, and short-term outcomes of this approach.Results: Technical success was achieved in 17 of 21 patients owing to 4 type I endoleaks at the end of the procedures. A total of 70 branch arteries were revascularized and 14 celiac trunks were covered intentionally without reconstruction. Of 7 intraoperative endoleaks, 2 were managed intraoperatively and 5 (4 type I and 1 type II) disappeared spontaneously within 1 month. No spinal cord or abdominal organ or limb ischemia was observed. Mean follow-up was 16.2±6.1 months. No death or type I or III endoleak occurred during the follow-up; 2 type II endoleaks were observed. Nineteen of the 21 false lumens thrombosed, and the total aortic diameter decreased (57.3±8.4 to 55.3±7.4 mm, p<0.01). Three (4.3%) of 70 target branch arteries occluded during follow-up. The cumulative patency of retrogradely and antegradely revascularized branch arteries was 97.3% vs 100% at 12 months and 91.2% vs 100% at 18 months.Conclusion: Total endovascular therapy with parallel stent-grafts could be an effective alternative in treating postdissection TAAA. Further studies with long-term follow-up and larger sample size are recommended to evaluate the technique.